Dialektika Keagamaan dan Kebangsaan dalam Tarekat Shiddiqiyyah - Nasih, Ahmad Munjin; Saputra, Meidi; Tasmuji, Tasmuji; Syakur, Abd. (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
The purpose of this study was to describe the history of the Shiddiqiyyah Tarekat, the forms of nationalism in the Shiddiqiyyah Tarekat, and the meeting point of religion and nationalism in the Shiddiqiyyah Tarekat. The research approach used a qualitative approach with a descriptive research type. The data collection techniques used were observation, in-depth interviews, and literature study. The results showed that the Shiddiqiyyah Tarekat was a tarekat with very rapid development and had its own uniqueness that was different from other Sufi groups or tarekat. The forms of nationalism of the shiddiqiyyah tarekat were the eight abilities that must be held, the national monument, the poetry of the source of the independence of the Indonesian nation and the establishment of the Unitary State of the Republic of Indonesia and the establishment of a brotherhood of love for the Indonesian homeland. The meeting point of religion and nationalism in the shiddiqiyyah tarekat was the concept of hubbul wathan minal iman, which means that love for the country was part of faith.